Memory-Efficient Byzantine Fault-Tolerant Replication for Highly Resource-Constrained Systems - Böhm, Harald; Distler, Tobias (1st Workshop on Resilient Operations – Byzantine Fault Tolerance and State-Machine Replication (ROBUST '24), 2024)
Recently, possible application scenarios of Byzantine fault tolerant (BFT) state-machine replication have been expanded to include highly resource-constrained nodes, with RAM of 1MB of or less. As memory is a scarce resource, using it efficiently is of utmost importance. In this paper, we show that the upper bound for memory demand of the PBFT protocol reported by previous work can be improved even further, by applying additional optimizations.<br